Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Đáp án của mình là:
3 ( |1 - x | - 2 ) + 1 = 7
3 ( |1 - x | - 2 ) = 7 - 1
3 ( |1 - x | - 2 ) = 6
1 - x - 2 = 6 : 3
1 - x - 2 = 2
1 - x = 2 + 2
1 - x = 4
x = 1 - 4
x = -3
nhé bạn!
__HT__
Ta có : \(\left(3-x\right)\left|x+5\right|=0\)
\(\Leftrightarrow\orbr{\begin{cases}3-x=0\\\left|x+5\right|=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=3\\x+5=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=3\\x=-5\end{cases}}\)
Ta có :
\(\left(3-x\right)\left|x+5\right|=0\)
\(\Rightarrow\orbr{\begin{cases}3-x=0\\\left|x+5\right|=0\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=3\\x+5=0\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=3\\x=-5\end{cases}}\)
a) (-2) . ( x+7 ) + (-5) = 7
<=>(-2).(x+7)=7+5
<=>x+7=12:(-2)
<=>x+7=-6
<=>x=(-6)-7
<=>x=-13
Vậy x=-13
b)(x+4) : (-7) = 14
<=>x+4=14 x (-7)
<=>x+4=-98
<=>x=-98-4
<=>x=-102
Vậy x= -102
c) 72 : ( x+5) - 4 = -12
<=>72:(x+5)=(-12)+4
<=>x+5=72:(-8)
<=>x+5=-9
<=>x=-9-5
<=>x=-14
Vậy x= -14
d) (x+3) : (-6 ) + 12 = 8
<=>(x+3) :(-6)=8-12
<=>x+3=(-4)x(-6)
<=>x+3=24
<=>x=24-3
<=>x=21
Vậy x= 21
\(\frac{x-5}{3}=\frac{6}{5}\)
\(x-5=\frac{6}{5}.3\)
\(x-5=\frac{18}{5}\)
\(x=\frac{18}{5}+5\)
\(\Rightarrow x=\frac{43}{5}\)
Vậy ...
\(\frac{1}{3}=\frac{2-x}{4}\)
\(\frac{4}{3}=2-x\)
\(x=2-\frac{4}{3}\)
\(\Rightarrow x=\frac{2}{3}\)
Vậy ...
a) => 4/3x = 7/9 - 4/9 = 1/3
=> x = 1/3 : 4/3 = 1/4
b) => 5/2 - x = 9/14 : (-4/7) = -9/8
=> x = 5/2 - (-9/8) = 5/2 + 9/8 = 29/8
c) => 3x = 2 và 2/3 - 3/4 = 8/3 - 3/4 = 23/12
=> x = 23/12 : 3 = 23/36
D) => -5/6 - x = 1/4
=> x = -5/6 - 1/4 = -13/12
a) \(\dfrac{4}{9}+\dfrac{4}{3}x=\dfrac{7}{9}\)
\(\dfrac{4}{3}x=\dfrac{7}{9}-\dfrac{4}{9}=\dfrac{1}{3}\)
\(x=\dfrac{1}{3}:\dfrac{4}{3}\)
\(x=\dfrac{1}{4}\)
b) \(\left(\dfrac{5}{2}-x\right)\left(-\dfrac{4}{7}\right)=\dfrac{9}{14}\)
\(\dfrac{5}{2}-x=\dfrac{9}{14}:\left(-\dfrac{4}{7}\right)=-\dfrac{9}{8}\)
\(x=\dfrac{5}{2}-\left(-\dfrac{9}{8}\right)\)
\(x=\dfrac{29}{8}\)
c) \(3x+\dfrac{3}{4}=2\dfrac{2}{3}\)
\(3x+\dfrac{3}{4}=\dfrac{8}{3}\)
\(3x=\dfrac{8}{3}-\dfrac{3}{4}=\dfrac{23}{12}\)
\(x=\dfrac{23}{12}:3\)
\(x=\dfrac{23}{36}\)
d) \(-\dfrac{5}{6}-x=\dfrac{7}{12}+\dfrac{-1}{3}\)
\(-\dfrac{5}{6}-x=\dfrac{1}{4}\)
\(x=-\dfrac{5}{6}-\dfrac{1}{4}\)
\(x=-\dfrac{13}{12}\)
c) 2x+(15-(7-4)2)=24.3
2x+(15-32)=16.3
2x+(15-9)=48
2x+6=48
2x=48-6
2x=42
x=42:2
x=21
Vậy...
a, 17+(-x)=-16-(-34)
<=> 17+(-x)= - 50
=> -x= - 33
=> x= 33
b, x-40=9.(-5)+9
<=> x-40= -36
=> x= 4
c, 2x + [ 15 - ( 7 - 4 ) 2 ] = 24 . 3
<=> 2x+ [ 15- 32 ] = 48
<=> 2x+4=48
=>2x=44
=>x=22
d, 1125-10x-3 = 152 - 102
=> 1125 - 10x-3 = 125
=> 10x-3 = 1000
=> 10x-3= 103
=> x-3=3
=>x=6
-2. ( x - 3 ) - ( x + 1 ) + 3 . ( 2 - x ) =5
<=>-2x+6-x-1+6-3x=5
<=>-2x-x-3x=5-6+1-6
<=>-6x=-6
<=>x=1
Vậy x=1
Ht